Exploring the management and mitigation of conflict between land owners and wind and solar PV developers. Similarly, how conflict resolution can be used to manage this interaction - Brimble, Benjamin (Department of Construction Economics and Management, 2025)
Wind farms, as one renewable energy technology, have an increasingly important role to play in the context of a rapid, and world-wide, move towards renewable energy. As wind farm projects are implemented, they will have an impact on an increasing number of communities around the country. It is mandatory for any large infrastructure project such as a wind farm to undergo an Environmental Impact Assessment (“EIA”) process. This must include a public participation component, wherein members of the effected community are allowed the opportunity to provide feedback and comment on the proposed development. This dissertation explores the link between subsequent community acceptance of wind farms and the initial sentiments expressed in project feasibility documentation, specifically EIA records and public participation processes. If community approval is inadequate, the implementation of wind farm projects will be in jeopardy. It is therefore critical to better understand the driver of community acceptance. The study follows a qualitative approach comprising a multiple case study design. Data is collected through semi-structured interviews with landowners adjacent to two operational wind farm projects, located in South Africa's Eastern and Western Cape provinces. This is combined with a comprehensive analysis of project EIA documentation. The results show a material contrast between subsequent acceptance levels and initial community sentiments. While both wind farms now demonstrate high levels of community acceptance, this differs significantly from the "cautious pessimism" evident in historical EIA records. Cross-case analysis between the two projects highlight how factors such as cumulative impacts of multiple wind farms in an area, socio-economic conditions, and construction management practices significantly influence acceptance levels. The results show that while EIAs provide an important baseline for predicting community acceptance of wind farm projects, they likely do not fully capture the dynamic factors affecting long-term community sentiment. The study illustrates that construction phase impacts, although temporary in nature, plays a crucial role in shaping community perceptions. This was not fully anticipated in the EIA documentation. These findings contribute to the broader understanding of how community acceptance evolves throughout a wind farm's lifecycle and suggest that EIAs should be viewed as living documents rather than static predictions of a particular point in time. The research recommends implementing ongoing stakeholder engagement beyond the initial EIA phase, developing adaptive management strategies to address emerging community concerns, and enhancing public participation methods to better prepare communities for wind farm development impacts.